2003
DOI: 10.1212/01.wnl.0000046586.38284.60
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pneumonia on mortality among patients hospitalized for acute stroke

Abstract: In this large community-wide study of stroke outcomes, pneumonia conferred a threefold increased risk of 30-day death, adding impetus to efforts to identify and reduce the risk of pneumonia in patients with stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
360
5
12

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 489 publications
(396 citation statements)
references
References 26 publications
19
360
5
12
Order By: Relevance
“…This is best done in a dedicated stroke unit with experienced staff and early mobilization 12,13,14 . Pneumonia is the leading cause of death in the post-acute phase of stroke 6 . The majority of the pneumonias are caused by aspiration but there are other reasons that include hypostatic pneumonia due to poor caring and immobilization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is best done in a dedicated stroke unit with experienced staff and early mobilization 12,13,14 . Pneumonia is the leading cause of death in the post-acute phase of stroke 6 . The majority of the pneumonias are caused by aspiration but there are other reasons that include hypostatic pneumonia due to poor caring and immobilization.…”
Section: Discussionmentioning
confidence: 99%
“…Our cohort showed the relationship between pneumonia and hemorrhagic stroke, probably because these patients had more complications during the hospitalization and more deaths than ischemic group. Some studies have demonstrated that complications such as stroke progression or pneumonia adversely affect clinical outcome 6,17 . Increase risk of poor outcome in patients with pneumonia, if unadjusted, reflects not only the effect of pneumonia but the effect of other factors predisposing them to pneumonia, such as initial stroke severity or neurological complications.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral stroke and concurrent pneumonia may increase the fatality rate of patients in 30 days by 4 folds, extend the length of hospital stay by 3 folds, and result in a sharp increase of medical expenses. [5][6][7] The clinical features of SAP are:…”
Section: Discussionmentioning
confidence: 99%
“…14 In our study, especially animals with signs of infection had a lower chance for survival, which is corresponding to the clinical Preventive antibiotic treatment in experimental stroke S Hetze et al situation, where mortality is approximately threefold higher in infected patients than in noninfected. 4 Especially, pneumonia is one of the most prominent reasons for death after stroke. 3,31 Clinical evidence and animal experiments indicate weight loss as a common phenomenon after stroke, and several pathways of metabolic imbalance were proposed to contribute to this phenomenon.…”
Section: Discussionmentioning
confidence: 99%